The Roles of circMTO1 in Cancer - Liu, Wei; Xiong, Yuanyuan; Wan, Renhua; Shan, Renfeng; Li, Jianfeng; Wen, Wu (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs (circRNAs) are a recently discovered type of non-coding RNAs with covalently closed circular structure, mainly formed by non-sequential back-splicing of precursor mRNAs (pre-mRNAs). Recent studies have demonstrated that circRNAs can have either oncogenic or tumor-suppressor roles depending on the cellular context. CircRNA mitochondrial tRNA translation optimization 1 (circMTO1), a recently reported circular RNA originating from exons of MTO1 located on chromosome 6q13, was proved to be abnormally expressed in many malignant tumors, such as hepatocellular carcinoma, gastric carcinoma and colorectal cancer, resulting in tumor initiation and progression. However, there are no reviews focusing on the roles of circMTO1 in cancer. Here, we first summarize the main biological characteristics of circMTO1, and then focus on its biological functions and the possible underlying molecular mechanisms. Finally, we summarize the roles of circMTO1 in cancer and discuss future prospects in this area of research.